2021
DOI: 10.21203/rs.3.rs-982158/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related Gene Signature For Clinically Predicting Recurrence After Hepatectomy of Hepatocellular Carcinoma Patients.

Abstract: Background: The high HCC recurrence rate was the main reason for the poor prognosis after hepatectomy. In this present study, we identified a novel ferroptosis-related gene signature for clinically predicting HCC recurrence after hepatectomy.Methods: Ferroptosis-related genes were obtained from the FerrDb database. We identified the ferroptosis-related differentially expressed genes (FDEGs) between HCC tissues and normal tissues from the GSE14520 dataset. These FDEGs were used to perform a univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress (26). In recent years, some studies focused on constructing oxidative stress or ferroptosis-related risk models for predicting patient survival and immune landscapes in various types of malignant tumors (27)(28)(29)(30)(31). However, few risk models were developed based on a combination of these two phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress (26). In recent years, some studies focused on constructing oxidative stress or ferroptosis-related risk models for predicting patient survival and immune landscapes in various types of malignant tumors (27)(28)(29)(30)(31). However, few risk models were developed based on a combination of these two phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, prognostic analysis suggested that higher PTGS2 expression may be associated with poor OS in OV, but the results of different studies were somewhat conflicting ( Steffensen et al, 2007 ). Moreover, SLC1A4, PCK2 and XBP1 were upregulated by 2-fold in erastin-treated HT-1080 cells ( Dixon et al, 2014 ) and could be used as powerful prognostic markers in hepatobiliary cancer ( Liu et al, 2020 ; Peng et al, 2021 ; Wang et al, 2022 ). As the key genes of ferroptosis, SLC3A2, MT1G and ACSL3 have also been widely explored in multiple FRG prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our own model to 12 other published HCC prognostic models to better show its predictive power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Multivariate analysis was used to calculate the risk value and prognostic evaluation for each dataset, leveling the playing field amongst the four models.…”
Section: New Model As a New Predictor Of Hccmentioning
confidence: 99%